Corneal nerve loss is related to the severity of painful diabetic neuropathy. (13th October 2021) - Kalteniece, Alise; Ferdousi, Maryam; Azmi, Shazli; Khan, Saif Ullah; Worthington, Anne; Marshall, Andrew; Faber, Catharina G.; Lauria, Giuseppe; Boulton, Andrew J. M.; Soran, Handrean; Malik, Rayaz A.
Abstract: Background and purpose: Previously it has been shown that patients with painful diabetic neuropathy (PDN) have greater corneal nerve loss compared to patients with painless diabetic neuropathy. This study investigated if the severity of corneal nerve loss was related to the severity of PDN. Methods: Participants with diabetic neuropathy ( n = 118) and healthy controls ( n = 38) underwent clinical and neurological evaluation, quantitative sensory testing, nerve conduction testing and corneal confocal microscopy and were categorized into those with no ( n = 43), mild ( n = 34) and moderate‐to‐severe ( n = 41) neuropathic pain. Results: Corneal nerve fibre density ( p = 0.003), corneal nerve fibre length ( p < 0.0001) and cold perception threshold ( p < 0.0001) were lower and warm perception threshold was higher ( p = 0.002) in patients with more severe pain, but there was no significant difference in the neuropathy disability score ( p = 0.5), vibration perception threshold ( p = 0.5), sural nerve conduction velocity ( p = 0.3) and amplitude ( p = 0.7), corneal nerve branch density ( p = 0.06) and deep breathing heart rate variability ( p = 0.08) between patients with differing severity of PDN. The visual analogue scale correlated significantly with corneal nerve fibre density ( r = −0.3, p = 0.0002), corneal nerve branch density ( r = −0.3, p = 0.001) and corneal nerve fibre length ( r = −0.4, p < 0.0001). Receiver operating curve analysis showed that corneal nerve fibre density had an area under the curve of 0.78 with a sensitivity of 0.73 and specificity of 0.72 for the diagnosis of PDN. Conclusions: Corneal confocal microscopy reveals increasing corneal nerve fibre loss with increasing severity of neuropathic pain and a good diagnostic outcome for identifying patients with PDN. Abstract : There is evidence that patients with painful diabetic neuropathy (PDN) have greater corneal nerve fibre loss compared to painless diabetic neuropathy. The current study investigated if the severity of corneal nerve loss was related to the severity of PDN. Corneal confocal microscopy shows increasing corneal nerve fibre loss with increasing severity of neuropathic pain and a good diagnostic outcome for identifying patients with PDN.